Emerging roles and potential clinical applications of translatable circular RNAs in cancer and other human diseases - Hongliang Liu; Wenjing Hao; Jiao Yang; Yuliang Zhang; Xinfang Wang; Chunming Zhang (Genes and Diseases, 2023)
Circular RNAs (circRNAs) are a special class of single-stranded RNA molecules with covalently closed loops widely expressed in eukaryotic organisms. CircRNAs have long been considered to play important roles in various physiological and pathological processes as non-coding RNAs. However, circRNAs have recently garnered considerable attention due to their ability to be translated into peptides/proteins via internal ribosome entry site- or N6-methyladenosine-mediated pathways or rolling translation mechanisms. Furthermore, dysregulation of translatable circRNAs and their encoded proteins has been associated with developing and progressing diseases such as cancer. This review aims to summarize the driving mechanisms of circRNA translation and the available strategies in circRNA translation research. The main focus is on the emerging biological functions of translatable circRNAs, their regulatory mechanisms, and potential clinical applications in human diseases to provide new perspectives on disease diagnosis, prognosis, and targeted therapy.